Uptake of skillfull thinking infusion among selected year four science teachers through steps / Bavani Nageswana Row - Bavani , Nageswana Row (2018)
This study explored selected teachers infusion of skillful thinking (ST) into Year Four Science subject matter. ST consists of three elements: teaching of various thinking skills, development of learners’ habits of mind and cultivation of metacognitive thinking among learners which should be taught simultaneously with subject matter. Though each element has many sub-elements, for the purpose of this study only one sub-element from each element was chosen. They were analysing information and ideas, habit of questioning and problem posing, and awareness in metacognitive thinking. The study was divided into two phases. Phase 1 consisted of gaining insight into teachers’ current ST practices and used these insights to prepare an educative material, Skillful Thinking Educative Pedagogical Support (STEPS) to support teacher learning in infusing ST for the topic ‘Properties of Materials’. Phase 2, the dominating phase for this study, was the implementation of STEPS that described changes in teachers’ practices of ST infusion and how STEPS had influenced the infusion of ST. In Phase 1, nine purposively selected Year 4 science teachers from schools in Negeri Sembilan participated. Qualitative data collection techniques such as semi-structured interviews with teachers, classroom observations and focused group interviews with students were employed. Using constant comparative method, three themes emerged about the selected teachers’ ST practices. The themes were lack knowledge on ST, lack pedagogical skills of ST and poor classroom management. Based on these findings, STEPS was designed. STEPS was conceptualized as design heuristics that consisted of educative features that delivered recommendations and rationales on how the teachers might infuse ST into lessons. Three teachers from Phase 1 participated in Phase 2. Qualitative data collection techniques were employed as in Phase 1. Using constant comparative method three themes ‘teachers teach students to analyse information and ideas about properties of materials’, ‘developing students’ habit of asking questions and posing problems’ and ‘promoting students to be aware of their thinking and learning’ were identified. Within each of them, categories that showed unsatisfactory and satisfactory practices of ST were described. For example, for the first theme, at the unsatisfactory stage, the teachers spent more time in probing students’ content knowledge but at satisfactory stage, teachers began teaching students to gather information and ideas about properties of materials, modelling specific thinking strategies to analyse the information and teach to transfer learnt thinking strategies into new contexts. Findings of Phase 2 revealed that all three teachers, eventually were able to independently enact ST infused lessons by adapting recommendations provided in the STEPS. They enacted enhanced lessons that show solid infusion of all three elements of ST. To ensure that these enhancements were actually from the STEPS, this study also described how the educative features helped teachers in enhancing their practices of ST. The study does indicate that in designing support for teacher learning to infuse ST, focus should be on pedagogical areas in which teachers are found to be lacking. Implications of this study and recommendations for future research were discussed.